Achieving High Rate Performance in Layered Hydroxide Supercapacitor Electrodes. Issue 6 (19th November 2013) - Wang, Xu; Yan, Chaoyi; Sumboja, Afriyanti; Yan, Jian; Lee, Pooi See
<x xml:space="preserve">Abstract</x> Layered hydroxides (LHs) are promising supercapacitor electrode materials with high specific capacitances. However, they generally exhibit poor energy storage ability at high current densities due to their insulating nature. Nickel‐cobalt‐aluminum LHs are synthesized and chemically treated to form LHs with enhanced conductivity that results in greatly enhanced rate performances. The key role of chemical treatment is to enable the partial conversion of Co2+ to a more conductive Co3+ state that stimulates charge transfers. Simultaneously, the defects on the LHs caused by the selective etching of Al promoted the electrolyte diffusion within LHs. As a result, the LHs show a high specific capacitance of 738 F g−1 at 30 A g−1, which is 57.2% of 1289 F g−1 at 1 A g−1. The strategy provides a facile and effective method to achieve high performance LHs for supercapacitor electrode materials.